Role of clinical and morphological data in prediction of regional lymph node involvement in early-stage breast cancer - Yu. S. Shatova; L. N. Vashchenko; E. S. Bosenko; S. M. Bakulina; V. N. Kasyanenko; R. G. Luganskaya; N. S. Ratieva (Опухоли женской репродуктивной системы)
Objective: to evaluate the frequency of axillary lymph node metastasis (detected at routine pathomorphological examination) in order to determine the group of patients who do not require lymph node surgery.Materials and methods. We analyzed medical records of 485 patients with breast cancer and no signs (either clinical or instrumental) of regional lymph node involvement who underwent surgery at the first stage of their treatment.Results and conclusion. In patients with cN0 cancer, only the size of primary tumor ≤1 cm was found to be a significant factor indicating that regional lymph nodes are not involved (in addition to palpation, ultrasound, mammography, and spiral x-ray computed tomography of the chest). In patients with сТ1c cancer, the majority of standard immunohistochemical markers cannot yet be used as predictors of regional lymph node involvement. However, tumor differentiation grade G1 is rather an exclusion, which in combination with the size of the primary tumor сТ1c can also be considered as a significant prognostic factor.